2012
DOI: 10.1152/ajplung.00340.2011
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial stress affects rat alveolar type II cell signaling and gene expression

Abstract: .) showed that contact of alveolar epithelial type II cells with an air-liquid interface (I AL) leads to a paradoxical situation. It is a potential threat that can cause cell injury, but also a Ca 2ϩ -dependent stimulus for surfactant secretion. Both events can be explained by the impact of interfacial tensile forces on cellular structures. Here, the strength of this mechanical stimulus became also apparent in microarray studies by a rapid and significant change on the transcriptional level. Cells challenged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 77 publications
(108 reference statements)
1
17
0
Order By: Relevance
“…Recent observations demonstrated that besides tissue stretch, the air compartment (and thus the associated surface tension) is the most important physiological stimulus for surfactant release 37 , 38 , 69 . Thus, the creation of a confluent epithelial monolayer at the air–liquid interface is a key prerequisite for tissue-specific cell differentiation on the chip.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations demonstrated that besides tissue stretch, the air compartment (and thus the associated surface tension) is the most important physiological stimulus for surfactant release 37 , 38 , 69 . Thus, the creation of a confluent epithelial monolayer at the air–liquid interface is a key prerequisite for tissue-specific cell differentiation on the chip.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our earlier work, the new lung-on-chip is equipped with passive medium exchange that enables not only the reproduction of the cyclic mechanical stress, but also long-term cell culture at the air–liquid interface, and thus reproduces the unique aspects of the lung microenvironment even more closely. The details of the microenvironment have significant impacts on a wide range of biological processes, including epithelial cell polarity and cell differentiation, which in turn play important roles in determining physiological functions 32 38 . Furthermore, we describe a breathing lung alveolar barrier consisting of primary human alveolar epithelial and lung endothelial cells cultured in an in vivo –like environment.…”
Section: Introductionmentioning
confidence: 99%
“…type II alveolar epithelial cells via shear forces. Hence, interfacial stress alone can result in major dysfunction of type II alveolar epithelial cells as illustrated in in vitro test systems (Hobi et al 2012 ; Ravasio et al 2011 ).…”
Section: Function Under Normal Conditionsmentioning
confidence: 99%
“…A recent work employed microarray technology to demonstrate that interfacial stress leads to rapid and significant changes in the expression of genes involved in stress response and defense pathways (96). However, not only mechanical stimuli contribute to VILI pathogenesis.…”
Section: Mechanical Insults In Ali: Ventilator-induced Lung Injurymentioning
confidence: 99%